Producer-consumer-networks as drivers of sustainability transition in rural regions. Two cases from Costa Rica - Avendaño Leadem, Daniel (2024)
Successful sustainability transitions are crucial to answer to ongoing crises. Focusing strongly on biocultural heritage, local customs, and traditions, as well as the natural environment and landscape aesthetics, rural regions have great potential to promote sustainable development and growth. This sustainable development of rural regions further contributes not only to local, but also to national and supranational development by strengthening sustainable economic growth, alleviating unemployment, and poverty, and improving living conditions. Local entrepreneurs are continuously included in discussions on sustainability transitions in rural regions as an important driver through their innovative entrepreneurial activities. By comparing two example regions within rural areas of Costa Rica - the Dota and Turrialba region - the role of these entrepreneurial endeavors is illustrated. For this purpose, we exemplify how both regions contribute to rural, sustainable development based on their geographical, entrepreneurial, and collective characteristics. Specifically, the role of entrepreneurs’ specific mind- and skillset, their embeddedness in producer-consumer-networks and the encompassing geographical context is investigated. Implications on the different levels of analysis are drawn in terms of learning opportunities for both, the respective included regions, as well as supra-regional development in a broader sense. The sCoRe project is presented as an exemplary initiative designed to foster collaboration between rural entrepreneurs and academic initiatives to enhance local producer-consumer-networks, and thus contribute to the establishment of sustainable communities.